Comprehensive analysis of full genome sequence and Bd-milRNA/target mRNAs to discover the mechanism of hypovirulence in Botryosphaeria dothidea strains on pear infection with BdCV1 and BdPV1 - Wangcheng Hu; Hui Luo; Yuekun Yang; Qiong Wang; Ni Hong; Guoping Wang; Aiming Wang; Liping Wang (IMA Fungus)
Abstract Pear ring rot disease, mainly caused by Botryosphaeria dothidea, is widespread in most pear and apple-growing regions. Mycoviruses are used for biocontrol, especially in fruit tree disease. BdCV1 (Botryosphaeria dothidea chrysovirus 1) and BdPV1 (Botryosphaeria dothidea partitivirus 1) influence the biological characteristics of B. dothidea strains. BdCV1 is a potential candidate for the control of fungal disease. Therefore, it is vital to explore interactions between B. dothidea and mycovirus to clarify the pathogenic mechanisms of B. dothidea and hypovirulence of B. dothidea in pear. A high-quality full-length genome sequence of the B. dothidea LW-Hubei isolate was obtained using Single Molecule Real-Time sequencing. It has high repeat sequence with 9.3% and DNA methylation existence in the genome. The 46.34 Mb genomes contained 14,091 predicted genes, which of 13,135 were annotated. B. dothidea was predicted to express 3833 secreted proteins. In bioinformatics analysis, 351 CAZy members, 552 transporters, 128 kinases, and 1096 proteins associated with plant-host interaction (PHI) were identified. RNA-silencing components including two endoribonuclease Dicer, four argonaute (Ago) and three RNA-dependent RNA polymerase (RdRp) molecules were identified and expressed in response to mycovirus infection. Horizontal transfer of the LW-C and LW-P strains indicated that BdCV1 induced host gene silencing in LW-C to suppress BdPV1 transmission. To investigate the role of RNA-silencing in B. dothidea defense, we constructed four small RNA libraries and sequenced B. dothidea micro-like RNAs (Bd-milRNAs) produced in response to BdCV1 and BdPV1 infection. Among these, 167 conserved and 68 candidate novel Bd-milRNAs were identified, of which 161 conserved and 20 novel Bd-milRNA were differentially expressed. WEGO analysis revealed involvement of the differentially expressed Bd-milRNA-targeted genes in metabolic process, catalytic activity, cell process and response to stress or stimulus. BdCV1 had a greater effect on the phenotype, virulence, conidiomata, vertical and horizontal transmission ability, and mycelia cellular structure biological characteristics of B. dothidea strains than BdPV1 and virus-free strains. The results obtained in this study indicate that mycovirus regulates biological processes in B. dothidea through the combined interaction of antiviral defense mediated by RNA-silencing and milRNA-mediated regulation of target gene mRNA expression.